Evaluating the distribution of priority benthic habitats through a remotely operated vehicle to support conservation measures off Linosa Island (Sicily Channel, Mediterranean Sea). Issue 7 (23rd February 2021) - Romagnoli, Beatrice; Grasselli, Ferrante; Costantini, Federica; Abbiati, Marco; Romagnoli, Claudia; Innangi, Sara; Di Martino, Gabriella; Tonielli, Renato
Abstract: Explorations of the Mediterranean deep sea using remotely operated vehicles have shown that the sea bed hosts rich habitats, supporting high biodiversity. However, there have been only a few studies dealing with the southern part of the basin, leading to limited protection and conservation efforts in this area. This study aimed to explore the sea bed off Linosa Island (Sicily Channel, southern Mediterranean Sea), which is considered a 'sentinel area' for alien species and global environmental changes owing to its geographic position, thus deserving special attention. Remotely operated vehicle surveys, carried out in 2016 and 2017, were analysed to provide the first ecological characterization of benthic assemblages at depths −19 – −384 m around Linosa Island. Communities were dominated by three priority habitats, amounting to 39% of the almost 5 km of the sea floor that was surveyed. These are represented in the euphotic zone by Posidonia oceanica meadows and, at greater depth, by newly discovered dense coral forests and extended rhodolith/maërl beds. Sixteen habitat‐forming species included in the Red List of the International Union for Conservation of Nature (e.g. gorgonians Eunicella cavolini and Paramuricea clavata, and black corals Antipathella subpinnata and Leiopathes glaberrima ) were recorded, as well as individuals of Sargassum sp. at −100 m depth. The volcanic island of Linosa represents a small, naturally preserved area, with very limited human pressure, hosting rich marine benthic biodiversity. Given the high species and habitat richness, we recommend its inclusion in the Special Protected Areas of Mediterranean Importance project (United Nations Environment Programme) and suggest a redefinition of the existing marine protected area extension.